Augmented Reality Environments for Medical Imaging and Computer-Assisted Interventions 6th International Workshop, MIAR 2013 and 8th International Workshop, AE-CAI 2013, Held in Conjunction with MICCAI 2013, Nagoya, Japan, September 22, 2013. Proceedings - Liao, Hongen.; Linte, Cristian A.; Masamune, Ken.; Peters, Terry M.; Zheng, Guoyan. (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of two workshops MAIR/AE-CAI 2013, held in conjunction with MICCAI 2013, held in Nagoya, Japan, in September 2013. The 29 revised full papers presented were carefully reviewed and selected from 44 submissions. The papers cover a wide range of topics addressing the main research efforts in the fields of medical image formation, analysis and interpretation, augmented reality and visualization, computer assisted intervention, interventional imaging, image-guided robotics, image-guided intervention, surgical planning and simulation, systematic extra- and intra-corporeal imaging modalities, and general biological and neuroscience image computing.